The role of vitamin C in the prevention of pancreatic cancer: a systematic-review - Martínez-Domínguez, Samuel J.; Laredo, Viviana; García-Rayado, Guillermo (Frontiers in Nutrition, 2024)
The aim of this systematic review was to assess the role of vitamin C in the prevention of pancreatic cancer (PC). Methods: A comprehensive literature search was performed in PubMed, Embase and Web of Science up to August 2023, to identify randomized controlled trials (RCT), cohort studies and mendelian randomization studies based on prospective databases assessing the role of vitamin C in PC prevention. Results: A total of twelve studies including European and North-American participants were included: two RCT, three mendelian randomization (MR) studies and seven cohort studies. Both RCT showed high quality in Cochrane risk of bias tool. Only one cohort study had < 7 points in Newcastle Ottawa Scale. Both RCT found no association between the intake of 500 mg/day of vitamin C and the incidence of PC. Only one prospective cohort study found an association between vitamin C serum levels and a lower incidence of PC. The remaining cohort studies and MR studies found no association between dietary/supplements intake of vitamin C or circulating vitamin C levels and the incidence of PC. Conclusions: There is no supporting evidence that vitamin C prevents PC development. Future prospective quality studies including high-risk populations are needed.